Directed Assembly of Cellulose Nanocrystals in Their Native Solid‐State Template of a Processed Fiber Cell Wall. Issue 12 (6th May 2021) - Solala, Iina; Driemeier, Carlos; Mautner, Andreas; Penttilä, Paavo A.; Seitsonen, Jani; Leppänen, Miika; Mihhels, Karl; Kontturi, Eero
Abstract: Nanoparticle assembly is intensely surveyed because of the numerous applications within fields such as catalysis, batteries, and biomedicine. Here, directed assembly of rod‐like, biologically derived cellulose nanocrystals (CNCs) within the template of a processed cotton fiber cell wall, that is, the native origin of CNCs, is reported. It is a system where the assembly takes place in solid state simultaneously with the top‐down formation of the CNCs via hydrolysis with HCl vapor. Upon hydrolysis, cellulose microfibrils in the fiber break down to CNCs that then pack together, resulting in reduced pore size distribution of the original fiber. The denser packing is demonstrated by N2 adsorption, water uptake, thermoporometry, and small‐angle X‐ray scattering, and hypothetically assigned to attractive van der Waals interactions between the CNCs. Abstract : Cellulose microfibrils in the fiber cell wall are chemically cut by HCl gas hydrolysis into cellulose nanocrystals. As the cell wall morphology of oriented microfibrils is retained during the hydrolysis, the nanocrystals undergo templated assembly into a more orderly structure, leaving the matrix significantly less porous.